2021
DOI: 10.1007/s10668-021-01425-w
|View full text |Cite
|
Sign up to set email alerts
|

Innovative management accounting practices for sustainability of manufacturing small and medium enterprises

Abstract: The environment in which manufacturing small and medium enterprises operate has become very complex, and therefore manufacturing SME’s owners need to be aware of the impact their decisions have on the environment and society. The aim of the research was to identify which innovative management accounting practices can be integrated into manufacturing SMEs’ strategies to overcome the challenge of being blamed by stakeholders as contributors to social and environmental problems. Published articles were sourced fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 49 publications
(80 reference statements)
0
7
0
Order By: Relevance
“…Various studies focussing on EMA practices (EMAPs) in developing countries have been done, with much focus on material flow cost accounting (MFCA) [18][19][20]. Studies that researched EMAPs have also contributed to the discourse [20][21][22]. Other studies acknowledge that EMA adoption in developing countries is still an issue.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies focussing on EMA practices (EMAPs) in developing countries have been done, with much focus on material flow cost accounting (MFCA) [18][19][20]. Studies that researched EMAPs have also contributed to the discourse [20][21][22]. Other studies acknowledge that EMA adoption in developing countries is still an issue.…”
Section: Introductionmentioning
confidence: 99%
“…With this explanation, we can develop a new point of view that the implementation of sustainability accounting is part of an organizational strategy whose goal is to improve organizational performance from the context of social and environmental performance. For example, Nartey & Poll (2021) described the innovative management accounting practices for sustainability for SMEs in the manufacturing industry. Innovative management accounting practices can be used by management as part of organizational strategy.…”
Section: Resultsmentioning
confidence: 99%
“…This shows that a small business organization has good capacity and capability to implement sustainability accounting practices. For example, innovative management accounting practices that support the concept of sustainability have been implemented in small business organizations in the manufacturing sector (Nartey & Poll, 2021). This provides an argument that the management of small business organizations has creativity in implementing accounting systems within the organization so that the organization is able to implement the concept of sustainability.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Dlamini & Schutte (2021) also explores the usage of management accounting practices among SMEs in Zimbabwe and found that MSMEs often use cost and budgeting system as well as strategic management accounting system. According to Nartey & van der Poll (2021), innovative management accounting practices is also found to influence sustainability of manufacturing small and medium enterprises. Similarly, Alvarez et al (2021;Ahmad & Zabri, 2016;Ruiz & Collazzo, 2021) found that management accounting practice positively affects MSMEs performance.…”
Section: Figure 1 Number Of Msmes In West Java Province 2016 -2021mentioning
confidence: 99%